Projeto de um sistema embarcado de aquisição de dados com implementação e testes de sistema de telemetria - Bocci, Emanuel Damasceno (Universidade Federal de São Carlos, 2020)
Extension projects are a great gateway to the development of science and engineering in the university environment. The Baja SAE project is no different, as it allows different fields of engineering to be put to the test for the creation of an off-road vehicle that has the best possible performance, requiring, therefore, a great effort around the study and application of various engineering concepts. And in this context, the electronic project has a fundamental role, not only in the creation of a data acquisition system to measure the final performance of the car, but also serving as a support for the entire mechanical design, providing data through instrumentation of the subsystems for their optimization and improvement. This work aims to present the entire process of development of the electronic data acquisition system that uses an internal communication protocol and a telemetry system by the Baja team at the Federal University of São Carlos, through the use of some types of sensors for reading vehicle information, and then processing and present all of them for the evaluation of the car's performance in tests and during competitions organized by SAE Brasil. In addition to the studies related to the important themes of the subject of this work, the technologies used in each stage are also addressed, methodologies for the design of each measurement subsystem, the structure of the internal communication with the CAN automotive communication protocol, tests with the LoRa radio frequency for the implementation of telemetry seeking to define a data transmission over a greater distance compared to modules used in previous studies in the defined mobility application, and the development of the interface that presents the information in a more easy and intuitive way for the team in the box. The end result was the design of a robust system, which includes hardware and software, capable of obtaining and processing all the information necessary for the evaluation of the vehicle, sending in real time all the information to the team, and with the potential for its evolution and improvement, by adding new sensors or changing the ones already used.
Design of an embedded data acquisition system with telemetry system implementation and testing
Keywords: Baja; Eletrônica embarcada; Sensoriamento; Telemetria; Aquisição de dados; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO